The Influence of Martensitic Intercalations in Magnetic Shape Memory NiCoMnAl Multilayered Films - Andreas Becker; Daniela Ramermann; Inga Ennen; Björn Büker; Tristan Matalla-Wagner; Martin Gottschalk; Andreas Hütten (Entropy, 2021)
Hysteresis and transformation behavior were studied in epitaxial NiCoMnAl magnetic shape memory alloy thin films with varying number martensitic intercalations (MIs) placed in between. MIs consists of a different NiCoMnAl composition with a martensitic transformation occurring at much higher temperature than the host composition. With increasing number of intercalations, we find a decrease in hysteresis width from 17 K to 10 K. For a large difference in the layers thicknesses this is accompanied by a larger amount of residual austenite. If the thicknesses become comparable, strain coupling between them dominates the transformation process, which manifests in a shift of the hysteresis to higher temperatures, splitting of the hysteresis in sub hysteresis and a decrease in residual austenite to almost 0%. A long-range ordering of martensite and austenite regions in the shape of a 3D checker board pattern is formed at almost equal thicknesses.